Determining Some Factors of the Financial Situation in the European Union Publishing Sector - Ángel Sanz José; María Bedate Ana; Mariano Durántez (Review of Economic Perspectives, 2018)
The publishing sector is probably a cultural industry with one of the greatest economic projections due to its huge turnover and contribution to the Gross Domestic Product of countries. In order to gain a better understanding of this sector, this paper examines a sample of the most important companies belonging to this sector in the European Union, focusing on studying their economic-financial profile. In order to achieve this, multivariate statistical techniques are used to create indicators on the evolution of the main variables and financial ratios of these companies over recent years. The specific objectives are: to summarise the information in a smaller number of factors, which in turn enable us to construct a robust and reliable synthetic indicator; and investigate the relationship between the constructed index and different variables such as company age, size and localisation. The changes experienced in this sector are reflected in the obtained results and provide a richer understanding of cultural industries.
Keywords: C38; G00; Z11; 330; Financial Ranking; Financial Ratios; Publishing Sector; Synthetic Indicator